Penetrating Tracheal Injury in a Child from a Rooster Bite: A Rare and Unprecedented Case Report - Jadhav, Amitkumar; Singh, Ram Jeewan; Khedkar, Kiran; Jayakumar, TK (Pediatric Review: International Journal of Pediatric Research, 2025)
Abstract Penetrating tracheal injuries in the pediatric population are uncommon and are most frequently associated with high-energy trauma or animal attacks, such as dog bites¹. However, avian-related penetrating injuries are exceedingly rare, with no documented cases of tracheal injury caused by rooster bites found in the literature. This report presents a rare case of a 3-year-old child who sustained a tracheal perforation secondary to a rooster bite to the neck. The clinical presentation, diagnostic challenges, surgical intervention, and successful outcome are discussed. This case highlights the importance of early recognition and prompt management of rare penetrating neck injuries in children.